2018
DOI: 10.1002/path.5008
|View full text |Cite
|
Sign up to set email alerts
|

IGF1R signalling in testicular germ cell tumour cells impacts on cell survival and acquired cisplatin resistance

Abstract: Testicular germ cell tumours (TGCTs) are the most frequent malignancy and cause of death from solid tumours in the 20‐ to 40‐year age group. Although most cases show sensitivity to cis‐platinum‐based chemotherapy, this is associated with long‐term toxicities and chemo‐resistance. Roles for receptor tyrosine kinases other than KIT are largely unknown in TGCT. We therefore conducted a phosphoproteomic screen and identified the insulin growth factor receptor‐1 (IGF1R) as both highly expressed and activated in TGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Expression of IGF1R or even presence of activated IGF1R does not always signify cells that are susceptible to IGF1R inhibition. This is seen in the case of the seminoma cell line, TCAM2 (Selfe et al ., ), which despite comparatively high basal levels of activated IGF1R among TGCT cell lines was among the least responsive to an IGF1R TKI. Expression of other components of the IGF axis such as IRS2 and IGFBP5 has been shown to be important for determining sensitivity to an IGF1R mAb (Pavlicek et al ., ).…”
Section: Therapeutic Targeting Of the Igf System In Cancermentioning
confidence: 97%
See 3 more Smart Citations
“…Expression of IGF1R or even presence of activated IGF1R does not always signify cells that are susceptible to IGF1R inhibition. This is seen in the case of the seminoma cell line, TCAM2 (Selfe et al ., ), which despite comparatively high basal levels of activated IGF1R among TGCT cell lines was among the least responsive to an IGF1R TKI. Expression of other components of the IGF axis such as IRS2 and IGFBP5 has been shown to be important for determining sensitivity to an IGF1R mAb (Pavlicek et al ., ).…”
Section: Therapeutic Targeting Of the Igf System In Cancermentioning
confidence: 97%
“…Increased serum levels of IGF2 and IGFBP2 have been found in non‐seminomatous TGCT, decreasing upon successful therapy and increasing again in cases of recurrence (Fottner et al ., ). Our group has recently shown that IGF1R is expressed in approximately half of non‐seminomas and influences survival of non‐seminoma cells in vitro (Selfe et al ., ).…”
Section: Role Of Igf System In Oncogenesismentioning
confidence: 97%
See 2 more Smart Citations
“…Schlueter et al ., () showed that in zebrafish, knockdown of one of two functional copies of IGF1R gene resulted in disturbed migration and reduced number of PGCs colonizing the genital ridges. In a recent study, phosphorylation of IGF1R was detected in TGCT cell lines of non‐seminoma type and at highest levels of the RTKs (Selfe et al ., ). The insulin receptor, which can heterodimerize with IGF1R, was also found highly phosphorylated, in support of an active IGF pathway in TGCT.…”
Section: Igf1r Signallingmentioning
confidence: 97%